2015
DOI: 10.1093/icvts/ivv191
|View full text |Cite
|
Sign up to set email alerts
|

Continuous monitoring of cardiac function by 3-dimensional accelerometers in a closed-chest pig model

Abstract: Miniaturized 3D accelerometers placed on the heart can assess global and regional function in a closed-chest model. The technique may be used for continuous postoperative monitoring after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This may be relevant for assessing the effects of inotropic and chronotropic medications, especially in the situation in which a drug is added to an existing regimen. Hyler et al [9] and Grymyr et al [10] report similar responses of the epicardial accelerometer to catecholamine administration.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This may be relevant for assessing the effects of inotropic and chronotropic medications, especially in the situation in which a drug is added to an existing regimen. Hyler et al [9] and Grymyr et al [10] report similar responses of the epicardial accelerometer to catecholamine administration.…”
Section: Discussionmentioning
confidence: 86%
“…PEA provides continuous measurement of cardiac contractility, but it was not reported to monitor the twist–untwist motion of the heart. Hyler et al [9] and Grymyr et al [10] reported their experience with epicardial 3D accelerometer as a tool for detecting LV function in the experimental setting of post-cardiac surgery care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique may therefore represent a future clinical tool for the detection of complications and for the guidance of vasoactive and inotropic treatment during cardiac surgery. The usefulness of the accelerometer has been demonstrated in closed-chest situations [6], and a smaller device (2.0 mm) with an incorporated pacemaker lead is being developed. The multifunctional sensor will be placed and removed like ordinary pacemaker leads and thereby provides cardiac function monitoring postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated the applicability of this technique in continuous monitoring of LV function in open and closed-chest experimental studies, and in patients undergoing off-pump coronary artery bypass grafting [5][6][7]. Epicardial systolic velocity as revealed by the accelerometer correlates with echocardiographic measurements during coronary occlusion [8], and a great advantage of the accelerometer is that automated signal analysis is possible [9].…”
Section: Introductionmentioning
confidence: 99%